2021
DOI: 10.1002/jmv.27272
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on the mental health in a cohort of Italian rehabilitation healthcare workers

Abstract: The COVID‐19 pandemic has had a strong impact on healthcare workers (HCWs), affecting their physical and mental health. In Italy, HCWs have been among the first exposed to unprecedented pressure, dealing with large numbers of infections during the first pandemic wave. However, the severe psychological consequences on HCWs find little evidence in the literature, especially in terms of comparison to the status quo ante pandemic. The aim of this study was to provide an assessment of the mental health burden in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 66 publications
(130 reference statements)
1
51
1
4
Order By: Relevance
“…Of note, healthcare workers represented in this dataset are much more likely to be female, reflecting the fact that more women typically work in healthcare roles; however, as demonstrated in the tables, there was no statistically significant difference in reinfection or recurrence by sex. Given the increased odds of recurrence and reinfection noted in this study, special precautions and protections should prioritize clinical healthcare workers as they shoulder a large portion of disease, which is negatively affecting not only their physical health but mental health as well [ 28 ]. To start, individuals in high-exposure groups should continue to abide by previous public health precautions, irrespective of policy easement.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, healthcare workers represented in this dataset are much more likely to be female, reflecting the fact that more women typically work in healthcare roles; however, as demonstrated in the tables, there was no statistically significant difference in reinfection or recurrence by sex. Given the increased odds of recurrence and reinfection noted in this study, special precautions and protections should prioritize clinical healthcare workers as they shoulder a large portion of disease, which is negatively affecting not only their physical health but mental health as well [ 28 ]. To start, individuals in high-exposure groups should continue to abide by previous public health precautions, irrespective of policy easement.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies have showed a high prevalence of rehabilitative healthcare professionals’ burnout during the COVID-19 pandemic [ 35 , 36 ]. However, to the best of our knowledge, this is the first study investigating the impact that the psychosocial work environment might have on frustration perceived by physical therapists.…”
Section: Discussionmentioning
confidence: 99%
“…Physical therapists and all health care workers are among individuals with the highest risk of contracting the virus, considering that they are under an overwhelming psychological pressure, requiring manual contact with patients [ 35 , 41 , 43 , 48 ]. It has been proposed that focusing on lack of basic need satisfaction alone may be ineffective in adequately describing how negative work-related social factors impact employees’ psychological needs [ 17 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike prior outbreaks, the COVID-19 pandemic could have a potentially long-term psychological impact on both the general public and HCWs. One year following the start of the pandemic, few studies have been conducted to assess the psychological impact among HCWs using the Depression, Anxiety, and Stress Scale (DASS-21) questionnaire (9)(10)(11)(12)(13)(14)(15). Also, few longitudinal studies have been conducted to evaluate the long-term impact of the pandemic on health care providers (16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%